Probing structurally altered and aggregated states of therapeutically relevant proteins using GroEL coupled to bio‐layer interferometry. (28th July 2014) - Naik, Subhashchandra; Kumru, Ozan S.; Cullom, Melissa; Telikepalli, Srivalli N.; Lindboe, Elizabeth; Roop, Taylor L.; Joshi, Sangeeta B.; Amin, Divya; Gao, Phillip; Middaugh, C. Russell; Volkin, David B.; Fisher, Mark T.
Abstract The ability of a GroEL‐based bio‐layer interferometry (BLI) assay to detect structurally altered and/or aggregated species of pharmaceutically relevant proteins is demonstrated. Assay development included optimizing biotinylated‐GroEL immobilization to streptavidin biosensors, combined with biophysical and activity measurements showing native and biotinylated GroEL are both stable and active. First, acidic fibroblast growth factor (FGF‐1) was incubated under conditions known to promote (40°C) and inhibit (heparin addition) molten globule formation. Heat exposed (40°C) FGF‐1 exhibited binding to GroEL‐biosensors, which was significantly diminished in the presence of heparin. Second, a polyclonal human IgG solution containing 6–8% non‐native dimer showed an increase in higher molecular weight aggregates upon heating by size exclusion chromatography (SEC). The poly IgG solution displayed binding to GroEL‐biosensors initially with progressively increased binding upon heating. Enriched preparations of the IgG dimers or monomers showed significant binding to GroEL‐biosensors. Finally, a thermally treated IgG1 monoclonal antibody (mAb) solution also demonstrated increased GroEL‐biosensor binding, but with different kinetics. The bound complexes could be partially to fully dissociated after ATP addition (i.e., specific GroEL binding) depending on the protein, environmental stress, and the assay's experimental conditions. Transmission electron microscopy (TEM) images of GroEL‐mAb complexes, released from the biosensor, also confirmed interaction of bound complexes at the GroEL binding site with heat‐stressed mAb. Results indicate that the GroEL‐biosensor‐BLI method can detect conformationally altered and/or early aggregation states of proteins, and may potentially be useful as a rapid, stability‐indicating biosensor assay for monitoring the structural integrity and physical stability of therapeutic protein candidates.